Hybrid endoscopic submucosal dissection (ESD) compared with conventional ESD for colorectal lesions: a systematic review and meta-analysis - McCarty, Thomas R.; Bazarbashi, Ahmad Najdat; Thompson, Christopher C.; Aihara, Hiroyuki (Endoscopy, 2020)
Background Hybrid endoscopic submucosal dissection (ESD) is increasingly utilized to overcome the complexity of conventional ESD. This systematic review and meta-analysis evaluated the efficacy and safety of hybrid ESD for treatment of colorectal lesions.Methods Search strategies were developed in accordance with PRISMA guidelines. Pooled proportions were calculated with rates estimated using random effects models. Measured outcomes included en bloc resection, procedure-associated complications, recurrence, and need for surgery. Subgroup analyses were performed to compare effectiveness of conventional versus hybrid ESD.Results 16 studies (751 patients) were included with a mean (standard deviation [SD]) lesion size of 27.96 (10.55) mm. En bloc resection rate was 81.63 % (95 % confidence interval [CI] 72.07 – 88.44; I2 = 80.89). Complications, recurrences, and need for surgery occurred in 7.74 % (95 %CI 4.78 – 12.31; I2 = 65.84), 4.52 % (95 %CI 1.40 – 13.65; I2 = 76.81), and 3.64 % (95 %CI 1.76 – 7.37; I2 = 15.52), respectively. Mean procedure duration was 48.83 (22.37) minutes. On subgroup analyses comparing outcomes for conventional (n = 1703) versus hybrid ESD (n = 497), procedure duration was significantly shorter for hybrid ESD (mean difference 18.45 minutes; P = 0.003), with lower complication rates (P = 0.04); however, hybrid ESD had lower en bloc resection rates (P < 0.001). There was no difference in rates of recurrence or surgery (P > 0.05).Conclusion While hybrid ESD was safe and effective for removal of colorectal lesions, with shorter procedure duration, fewer complications, and no difference in recurrence versus conventional ESD, hybrid ESD was associated with a lower en bloc resection rate.